DOI: 10.14393/ufu.te.2020.326
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de sinais eletrofisiológicos e desenvolvimento de imunossensores para detecção de troponina T e proteína C reativa

Abstract: Este tutorial esta disponível em vídeo https://www.youtube.com/watch?v=hgAOoBdjsCo&t=1s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Both ceramic honeycombs and ceramic foams have been used as substrates on which different types of 1D nanostructures were created, using different approaches. These include carbon nanofibers (CNFs), [5][6][7][8][9][10][11][12][13] carbon nanotubes (CNTs), [14][15][16][17][18][19][20] or SiC nanofibers. 4,21 Previous works demonstrated that moderate (B30 m 2 /g) to high (B150 m 2 /g) values for the SSA could be obtained, depending on the amount, length, and diameter of the nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Both ceramic honeycombs and ceramic foams have been used as substrates on which different types of 1D nanostructures were created, using different approaches. These include carbon nanofibers (CNFs), [5][6][7][8][9][10][11][12][13] carbon nanotubes (CNTs), [14][15][16][17][18][19][20] or SiC nanofibers. 4,21 Previous works demonstrated that moderate (B30 m 2 /g) to high (B150 m 2 /g) values for the SSA could be obtained, depending on the amount, length, and diameter of the nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Women with PP are at risk of bleeding throughout pregnancy, especially in the third trimester. These patients also have an increased risk for peripartum hysterectomy, blood transfusion, postpartum hemorrhage, sepsis, and poor neonatal outcomes [4,15,16,17]. In this study, maternal and neonatal outcomes of pregnancies with PP uncomplicated with PAS that were subjected to by planned or emergency cesarean section were compared.…”
Section: Discussionmentioning
confidence: 99%
“…The XRD data obtained in the present study suggest that this maximum amount may vary depending on the synthesis route, which is in agreement with the previous studies. [6][7][8][9]12,13 Among the homogeneously precipitated powders, only the 5Fe1070T60t system is free from the a-Fe 2 O 3 and transitional Al 2 O 3 phases. No CNF was detected in the SEM analysis of the corresponding nanocomposite powder (R-5Fe1070T60t).…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, one of the main advantage of the starting oxide powders (a-Al 2À2x Fe 2x O 3 ) prepared by the homogeneous precipitation method followed by a calcination treatment is their higher SSA (19-34 m 2 /g- Table I) when compared with the catalytic materials prepared by other chemical routes, also followed by a calcination treatment (o10 m 2 /g). [6][7][8][9]12 Therefore, there is no need for milling and subsequently no potential of contamination. As in previous works, the main key is to find the appropriate calcination treatment (temperature and time) for the starting oxide powder with as high Fe content as possible to assure its complete crystallization under the corundum form while minimizing the amount of the hematite-rich secondary phase and maximizing the SSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation